A new standard in dementia knowledge measurement: Comparative validation of the Dementia Knowledge Assessment Scale and the Alzheimer’s Disease Knowledge Scale. - Annear, M.; Eccleston, C.; McInerney, F.; Elliott, K.; Toye, Christine; Tranter, B.; Robinson, A. (Wiley-Blackwell Publishing, Inc., 2015)
Objectives: To compare the psychometric performance of the Dementia Knowledge Assessment Scale (DKAS) and the Alzheimer's Disease Knowledge Scale (ADKS) when administered to a large international cohort before and after online dementia education. Design: Comparative psychometric analysis with pre- and posteducation scale responses. Setting: The setting for this research encompassed 7,909 individuals from 124 countries who completed the 9-week Understanding Dementia Massive Open Online Course (MOOC). Participants: Volunteer respondents who completed the DKAS and ADKS before (n = 3,649) and after (n = 878) completion of the Understanding Dementia MOOC. Measurements: Assessment and comparison of the DKAS and ADKS included evaluation of scale development procedures, interscale correlations, response distribution, internal consistency, and construct validity. Results: The DKAS had superior internal consistency, wider response distribution with less ceiling effect, and better discrimination between pre- and posteducation scores and occupational cohorts than the ADKS. Conclusion: The 27-item DKAS is a reliable and preliminarily valid measure of dementia knowledge that is psychometrically and conceptually sound, overcomes limitations of existing instruments, and can be administered to diverse cohorts to measure baseline understanding and knowledge change.